The impact of acquiring EU status on the earnings of East European migrants in the UK: Evidence from a quasi-natural experiment - Ruhs, M (Wiley, 2017)
On 1st May 2004, ten new states – including the “A8” countries in Central and Eastern Europe – joined the European Union (EU). This paper explores the impact of EU enlargement on A8 workers who were already working in the UK before 1st May 2004 – legally or illegally. More specifically, the paper analyses the impact of the change in the legal (immigration) status that A8 workers experienced on 1st May 2004 on their earnings in the UK. The empirical analysis employs difference-in-difference estimation using data obtained from a relatively small but unique survey of migrant workers from four of the A8 countries (Poland, Czech Republic, Slovakia, and Lithuania) and two other East European countries (the Ukraine and Bulgaria), carried out one month before and 6-8 months after EU enlargement in May 2004. The results of this exploratory analysis suggest a statistically significant and positive impact of acquiring EU status on earnings. The data further indicate that, in part, this effect was brought about by A8 workers gaining the right to freely change jobs after EU enlargement. There is no evidence of a ‘legalization effect’ on earnings.